Analisis Kebijakan Implementasi Kurikulum Merdeka di Madrasah - Sutri Ramah; Miftahur Rohman (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2023)
The independent curriculum (kurikulum merdeka) has been designed to strengthen the profile of Pancasila students consists of six elements: faith, fear of God Almighty, and noble character; global diversity; cooperation; independence; critical reasoning; and creativity. This research aims to analyze the implementation of independece curriculum carried out by madrasas through the decree of the Ministry of Religious Affair (KMA) Number 347 of 2022. The approach used by researchers is a library research with content analysis method. In this research primary data source such as books, journals, newspapers, and other documents. The results of this research conclude that implementation of independent curriculum (Kurikulum Merdeka) in madrasas required learning facilities and infrastructure. In addition, educators are needed to understand the curriculum, such as learning achievements (CP), learning objectives (TP), and learning objectives flow (ATP). Besides it, the teacher must be able to integrate the material learning with orientation to strengthen profile of Pancasila students rahmatan lil alamin (P5 PPRA). This qualitative research ultimately has limitations, considering that the results of this study do not reflect the implementation of an independent curriculum in a specific madrasa. Therefore, it is necessary to conduct more comprehensive research with field research